2016
DOI: 10.2298/tsci160224158p
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy and environmental quality of hard coal and natural gas in whole life cycle concerning home heating

Abstract: The use of coal is suspected to have high environmental impact. Natural gas is treated as more environmentally friendly with high methane content and lower emission factors. In order to calculate the environmental impact in the whole life cycle associated with combustion of coal and natural gas all stages from "cradle to grave" should be taken into account. In particular, the transportation stage, especially in the case of life cycle analysis of gas, seems to be crucial. The distance of transmission of gas fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Natural gas is considered to be a cleaner source of electricity than coal because it produces lower CO 2 , SO 2 , and NO x emissions [23]. Emitted CO 2 , SO 2 , and NO x increase global warming potential and terrestrial acidification, among other effects [24]. As a result, a large benefit in terms of global warming potential and terrestrial acidification impact was shown for the 2020 and 2025 OEdelta values.…”
Section: Recipe2016 Midpoint Resultsmentioning
confidence: 99%
“…Natural gas is considered to be a cleaner source of electricity than coal because it produces lower CO 2 , SO 2 , and NO x emissions [23]. Emitted CO 2 , SO 2 , and NO x increase global warming potential and terrestrial acidification, among other effects [24]. As a result, a large benefit in terms of global warming potential and terrestrial acidification impact was shown for the 2020 and 2025 OEdelta values.…”
Section: Recipe2016 Midpoint Resultsmentioning
confidence: 99%
“…Similarly Rokni proposed a thermoeconomic analysis of a complex system, including biomass gasification, a solid oxide fuel cell and a Stirling engine, considering it in stationary operation and thus calculating cost rates for each material stream and energy flow [104]. From this viewpoint, the paper by Pikon et al [105] certainly introduced some methodological novelty, discussing some elements of thermoecologic cost accounting for the home heating sector. However, in this cited paper the analysis was carried out following a life cycle perspective and the critical aspects of thermoeconomic applciations in systems with unsteady operation did not emerge.…”
mentioning
confidence: 99%